CLINICAL AND MOLECULAR RESULTS OF SIX CASES WITH ROBERTS SYNDROME: REVIEW OF CASES FROM TURKIYE - Ayça Dilruba Aslanger; Tuğba Kalaycı; Esma Nur Konur; Çağrı Güleç; Şahin Avcı; Umut Altunoğlu; Volkan Karaman; Güven Toksoy; Birsen Karaman; Seher Başaran; Zehra Oya Uyguner; Gözde Yeşil Sayın (İstanbul Tıp Fakültesi Dergisi)
Objective: Roberts syndrome is a rare autosomal recessive disease characterized by limb defects, prenatal onset growth retardation, and craniofacial anomalies. We aimed to compare the clinical and molecular findings of six cases with Roberts syndrome with the previously reported patients from Turkiye and to emphasize that a definitive diagnosis can be made in the intrauterine period with cytogenetic tests in the early period without the need to wait for molecular test results. Materials and Methods: Six cases, diagnosed with Roberts syndrome, in our outpatient clinic of Istanbul University, Istanbul Faculty of Medicine, Medical Genetics Department between 2015-2021, were included in the study. The family history, clinical information, and cytogenetic and molecular findings of the patients were retrospectively reviewed and compared with the cases reported from Turkiye in the literature. G and C-banding techniques and Sanger sequencing of the ESCO2 gene were performed. Results: Pathogenic variants in homozygous in four and compound heterozygous in two patients in the ESCO2 gene were identified. Compound heterozygous c.[417dup];[1131+1G>A] (p.[(Pro140Thrfs*8)];[(?)]) in case 1, and c.[1111dup];[760del] (p. [(Thr371Asnfs*32)];[(Thr254Leufs*13)]) in case 6, homozygous c.1131+1G>A (p.(?)) in case 2, case 3 and case 5, and homozygous c.1111dup (p.(Thr371Asnfs*32)) in case 4 were detected. The variants reported in our case series were previously associated with the disease. The first demonstration of the c.760del in a Turkish case contributed to the genetic association of this pathogenic variants with Roberts syndrome Although all the previously reported patients were homozygous, we have detected two patients with compound heterozygous pathogenic alterations from Turkiye indicating that the disease should also be considered in families with no consanguinity.